How Do Social Media Marketing and Brand Equity Drive Consumer Purchasing Decisions in the Food Industry? - Handrimurtjahjo, Agustinus Dedy; Verencia, Corinne; Salwa, Siti (Universitas Mercu Buana, 2025)
Objectives: To create a solid and well-liked brand in the minds of consumers, businesspeople use Social Media Marketing to convey their messages. However, few studies have examined the impact of social media marketing and brands on purchase decisions. Prior studies use brand trust as a mediator in the relationship between social media marketing and purchase decisions. Meanwhile, Brand Equity as a way to express brand image and brand awareness has not received much attention as a determining factor in the relationship between social media marketing and purchasing decisions. This study aims to examine the effectiveness of social media marketing activities in influencing purchase decisions of the food industry (fried chicken) and the role of brand equity as a mediator in the relationship. Methodology: This study adopted descriptive quantitative research methods. The population comprises customers who frequently buy fried chicken in Indonesia and are selected using nonprobability and purposive sampling techniques. Data were collected using an online survey of 301 respondents. The partial least squares structural equation model (PLS-SEM) was used to test the hypotheses.Findings: The findings indicate that social media marketing activities (entertainment, interaction, customization, trendiness, and e-WOM) have a positive and significant effect on brand equity. Brand equity, consisting of brand image and awareness, also positively and significantly affects purchase decisions. Moreover, the results suggest that brand equity positively and significantly mediates the effect of social media marketing activities on purchase decisions. Conclusion: This study contributes to the marketing literature by using social media marketing activity variables to examine their effects on brand equity and purchase decisions in the fried chicken context. According to the study's findings, brands that engage in social media marketing activities can improve consumer purchasing decisions in Indonesia’s food industry. The results of this study imply that fried chicken business owners increase the intensity of their content on social media to provide product information, tips and tricks, games or quizzes, and interactions with consumers to increase traffic, brand image, and brand awareness. Fried chicken business owners can also use social media to ask for feedback and reviews from customers who have purchased their branded products. Reviews and testimonials from previous customers influence the purchasing decisions of potential customers who buy the brand's products.